Critical remarks on some applications of digital image analysis with emphasis on statistical methodology - Mohd. Rijal, Omar; Mohd. Noor, Norliza; Chang, Yun Fah (Penerbit UTM Press, 2001)
The results of Rijal and Noor [1] and [2] regarding the use of statistical methods and sources of uncertainty associated with making inferences when using digital images provide the motivation for this study. In this paper three other examples are presented with the purpose of providing an overview of applications (possibly statistical) of image analysis, and general issues highlighted. One conclusion from this study is that statistical/mathematical methodology should be emphasized in digital image analysis.